2017
DOI: 10.1186/s13036-017-0071-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the architecture of the regulatory system controlling methylenomycin production in Streptomyces coelicolor

Abstract: BackgroundThe antibiotic methylenomycin A is produced naturally by Streptomyces coelicolor A3(2), a model organism for streptomycetes. This compound is of particular interest to synthetic biologists because all of the associated biosynthetic, regulatory and resistance genes are located on a single cluster on the SCP1 plasmid, making the entire module easily transferable between different bacterial strains. Understanding further the regulation and biosynthesis of the methylenomycin producing gene cluster could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In S. coelicolor A3(2), these five genes are responsible for regulation of methylenomycin biosynthesis: mmyR and mmfR both code for TetR-like transcriptional repressors; mmfLHP are responsible for the biosynthesis of signalling molecules, known as methylenomycin furans (MMFs) that trigger production of the methylenomycin antibiotics 9. A mathematical model that explains in detail the methylenomycin regulatory system involving these five genes has been developed and matched with experimental data 20. In previous studies we have exploited this regulatory cassette and shown that inactivation of the mmyR -like transcriptional repressors is an effective approach for derepressing silent gene clusters in actinomycetes 10,12…”
Section: Resultsmentioning
confidence: 99%
“…In S. coelicolor A3(2), these five genes are responsible for regulation of methylenomycin biosynthesis: mmyR and mmfR both code for TetR-like transcriptional repressors; mmfLHP are responsible for the biosynthesis of signalling molecules, known as methylenomycin furans (MMFs) that trigger production of the methylenomycin antibiotics 9. A mathematical model that explains in detail the methylenomycin regulatory system involving these five genes has been developed and matched with experimental data 20. In previous studies we have exploited this regulatory cassette and shown that inactivation of the mmyR -like transcriptional repressors is an effective approach for derepressing silent gene clusters in actinomycetes 10,12…”
Section: Resultsmentioning
confidence: 99%
“…These results can provide answers to experimental hypotheses and hence inform the planning and enactment of subsequent experimental studies, saving time and resources. The dissemination of mathematical modelling approaches is important in establishing a wide-ranging archive of useful tools for the design and implementation of novel circuitry across synthetic biology [40][41][42][43][44][45]. In this paper, we present the first mechanistic mathematical model of the 2-input BLADE platform developed in [8].…”
Section: Introductionmentioning
confidence: 99%
“…These results can provide answers to experimental hypotheses and hence inform the planning and enactment of subsequent experimental studies, saving time and resources. The dissemination of mathematical modelling approaches is important in establishing a wide-ranging archive of useful tools for the design and implementation of novel circuitry across synthetic biology [39][40][41][42][43][44]. In this paper, we present the first mechanistic mathematical model of the 2-input BLADE platform developed in [8].…”
Section: Introductionmentioning
confidence: 99%